THE IMPACT OF CUSTOMER RELATIONSHIP MANAGEMENT ON COMPANY PERFORMANCE IN THREE SEGMENTS - Ismi Alawiyah; Putri Nadila Humairoh (Universitas Gunadarma, 2017)
Application of modern CRM as a kind of business intelligence successfuly become another resources factor which can improving company performance. The company's observed performance are financial performance, marketing performance, and operational performance. This study used literature review analyzing and elaborating the results of literture, books, and previous research. This research using literature review method and analyzed about twenty previous journals, supported by some of literature and books. Based on the result of the study, utilization of CRM implementation effectively and efficiently will increase companies performance in significant, specifically in financial, marketing, or operational performance. From all previous journal observed, the most dominant journal is about significant effect of CRM on marketing and financial performance. Keywords: CRM, financial performance, marketing performance, operational performance.